Emotionally and Biased on the Anniversary of ‘Slavic Dialogues’ - Elena Getova; Lilia Ivanova (Zeszyty Cyrylo-Metodiańskie)
A personal assessment of the achievements and scholarly contributions of the Slavic Dialogues journal of the Plovdiv University, on the occasion of its twentieth anniversary. Original title in Bulgarian: За юбилея на „Славянски диалози“ – емоционално и пристрастно.